Anticholinergic therapy: A case-based approach - Dudley Robinson; George Araklitis (Elsevier, 2020)
Anticholinergic medication remains integral in the management of women with Overactive Bladder syndrome although there is increasing evidence to support a link with the impairment of cognitive function. This editorial will review the available evidence and discuss the management of patients in order to minimise anticholinergic burden with a particular focus on the elderly. Keywords: Overactive bladder, Anticholinergic, Antimuscarinic, Cognitive function